Scale-bearing nanoflagellates from southern Tasmanian coastal waters, Australia. II. Species of Chrysophyceae (Chrysophyta), Prymnesiophyceae (Haptophyta, excluding Chrysochromulina ) and Prasinophyceae (Chlorophyta) - Leroi, JM; Hallegraeff, GM (Botanica Marina, 2006)
Twenty-eight species of scale-bearing nanoflagellates from southern Tasmanian waters are illustrated and discussed (excluding the haptophyte Chrysochromulina, previously reported (LeRoi and Hallegraeff 2004), and coccolithophorids). Scale morphologies of both field samples and enrichment cultures were examined using transmission electron microscopy. Predominant species included the chrysophyte Paraphysomonas imperforata, the prasinophyte Pyramimonas grossii, and haptophytes Phaeocystis globosa and Imantonia rotunda. There were nine new records for Australian waters: the chrysophytes Chrysolepidomonas marina, Paraphysomomas antarctica, P. bandaiensis, P. foraminifera, P. cf. takahashii, Petasaria heterolepis, Thaumatomastix cf. thomsenii, and the prasinophytes Dolichomastix cf. tenuilepis and Mamiella gilva. Two potentially harmful haptophyte species, Phaeocystis globosa and Prymnesium parvum f. patelliferum, responsible for bloom events and fish mortalities, particularly in the northern hemisphere, were also found. The present survey adds further evidence for the apparent cosmopolitanism of many scale-bearing nanoflagellate species. 2006 by Walter de Gruyter.